Utilization of GIS for the evaluation of visitor travel patterns after signage treatments at the Tallgrass Prairie National Preserve - Cochran, Amy (Kansas State University, 2021)
Understanding visitor travel patterns provides objective information for managers that supports efforts for sustaining the resources as well as visitor experiences through interpretation or signage. However, there is little objective evaluation of visitor travel patterns related to the effectiveness of messaging and park signage. This study was conducted to determine: 1) how does signage affect visitor concentrations; 2) how does directional signage affect visitors’ time allocation; and 3) how does directional signage affect visitor travel directionality at signage locations. Visitor travel patterns after signage manipulation were investigated at the Tallgrass Prairie National Preserve (TAPR) from September 2019 to November 2019. TAPR, a National Park Service unit located in east, central Kansas offers over 11,000 acres of prairie ecosystem, hiking trails, historic buildings, visitor center, and a small bison herd for viewing. Researchers used stratified random sampling to distribute GPS data loggers to all travel parties who voluntarily participated. Researchers sampled on weekends, weekdays, events, and holidays to better understand the differences in visitor-use patterns over a variety of days. A total of 91 visitors voluntarily participated in the study resulting in a 75% response rate. Results found that signage treatments were not effective in the way researchers expected for dispersing visitors towards desired locations, increasing overall time, and directing visitors to targeted locations. The findings give valuable objective information to managers, who can then better understand their visitors’ and plan where to focus messaging and interpretive efforts.
Keywords: Visitor travel patterns; GIS